2021
DOI: 10.1080/1461670x.2021.1922303
|View full text |Cite
|
Sign up to set email alerts
|

Local Newspapers’ Transition to Online Publishing and Video Use: Experiences from Norway

Abstract: This paper traces convergence and innovation processes in five local newspapers in the Inland Norway region. It is an explorative bottomup study of how local legacy newspapers' use of digital technology relates to organisational factors and business models, as well as their journalism. Based on interviews with chief editors and video journalists, the paper shows that these local newspapers adapted in specific ways, sometimes differ from their national counterparts. Each newspaper established a web-edition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The content analysis suggests that the three types of organizations each offer a distinct video storytelling style. As DOI would predict, organizations use digital affordances in ways that reflect organizational values and their ability to re-tool their practices (Puijk et al, 2021;Rogers, 2003). As previous research has found (Bock, 2012b) that LP organizations tend to post subject-driven videos without scripted narrative, while TV organizations copy reporter packages straight from newscasts to the web.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The content analysis suggests that the three types of organizations each offer a distinct video storytelling style. As DOI would predict, organizations use digital affordances in ways that reflect organizational values and their ability to re-tool their practices (Puijk et al, 2021;Rogers, 2003). As previous research has found (Bock, 2012b) that LP organizations tend to post subject-driven videos without scripted narrative, while TV organizations copy reporter packages straight from newscasts to the web.…”
Section: Resultsmentioning
confidence: 97%
“…Journalists who decide to change may co-opt innovation to extend their routines and ideals (Lewis, 2012). For instance, Puijk et al (2021) found journalists in Norway resisted the additional work posed by video and other technologies. Singer (2004aSinger ( , 2004b) noted existing organizational demands do not go away when an innovation like video production is adopted, and journalists may perceive such change as additional work.…”
Section: Diffusion Of Innovations Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Puijk, et al (2021) investigated the processes of convergence and innovation in five local newspapers in the inner region of Norway. Through an exploratory study on how the use of old local newspapers for digital technology is linked to organizational factors and business models, the study found that these local newspapers have adapted in certain ways, sometimes differing from their national counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Norwegian research shows that larger media groups can afford specialised expertise and share innovation (Puijk et al, 2021). In recent years, Swedish media groups have invested heavily in developing data analysis, almost annually acclaimed at the International News Media Association (INMA) awards, such as Best Use of Data Analytics or Research (Mittmedia 2020), Best Initiative to Retain Subscribers (Expressen 2021), Best Internal Data Dashboard and Reports (NTM, 2022), and Best Innovation in Newsroom Transformation (VK, 2022).…”
Section: The Case Of Swedenmentioning
confidence: 99%